Influence of Internal and External Controlling Teaching Behaviors on Students’ Motivational Outcomes in Physical Education: Is There a Gender Difference? - Abós, Ángel; Burgueño, Rafael; García-González, Luis; Sevil-Serrano, Javier (Human Kinetics, 2022)
Purpose: Grounded in self-determination theory, this study examined gender latent mean differences in students’ perceptions of externally and internally controlling teaching behaviors, basic psychological need frustration, controlled motivation, amotivation, and oppositional defiance in the physical education context. Moreover, it analyzed the differentiated role that internal and external controlling behaviors play on these self-determination theory-related variables among girls and boys. Method: A sample of 1,118 students (Mage = 14.11 ± 1.50; 50.9% girls) participated in this research. A multigroup structural equation modeling approach was used to respond to the research questions. Results: Analyses revealed that girls reported more maladaptive outcomes in most self-determination theory-related variables than boys. Although externally and internally controlling behaviors of physical education teachers were positively related to maladaptive outcomes, the behaviors correlate differently between boys and girls. Conclusion: Findings highlight the importance of reducing externally controlling behaviors in boys and internally controlling behaviors in both genders, but particularly in girls.
https://openpolicyfinder.jisc.ac.uk/id/publication/12256?from=single_hit
Keywords: Pedagogía; Motivación (Psicología); Diferencias sexuales (Psicología); Self-determination theory; Need-thwarting teaching; Motivation; Basic psychological needs; Sex